Reawakening the Intrinsic Cardiac Regenerative Potential: Molecular Strategies to Boost Dedifferentiation and Proliferation of Endogenous Cardiomyocytes - Bongiovanni, Chiara; Sacchi, Francesca; Da Pra, Silvia; Pantano, Elvira; Miano, Carmen; Morelli, Marco Bruno; D'Uva, Gabriele (Frontiers in Cardiovascular Medicine, 2021)
Despite considerable efforts carried out to develop stem/progenitor cell-based technologies aiming at replacing and restoring the cardiac tissue following severe damages, thus far no strategies based on adult stem cell transplantation have been demonstrated to efficiently generate new cardiac muscle cells. Intriguingly, dedifferentiation, and proliferation of pre-existing cardiomyocytes and not stem cell differentiation represent the preponderant cellular mechanism by which lower vertebrates spontaneously regenerate the injured heart. Mammals can also regenerate their heart up to the early neonatal period, even in this case by activating the proliferation of endogenous cardiomyocytes. However, the mammalian cardiac regenerative potential is dramatically reduced soon after birth, when most cardiomyocytes exit from the cell cycle, undergo further maturation, and continue to grow in size. Although a slow rate of cardiomyocyte turnover has also been documented in adult mammals, both in mice and humans, this is not enough to sustain a robust regenerative process. Nevertheless, these remarkable findings opened the door to a branch of novel regenerative approaches aiming at reactivating the endogenous cardiac regenerative potential by triggering a partial dedifferentiation process and cell cycle re-entry in endogenous cardiomyocytes. Several adaptations from intrauterine to extrauterine life starting at birth and continuing in the immediate neonatal period concur to the loss of the mammalian cardiac regenerative ability. A wide range of systemic and microenvironmental factors or cell-intrinsic molecular players proved to regulate cardiomyocyte proliferation and their manipulation has been explored as a therapeutic strategy to boost cardiac function after injuries. We here review the scientific knowledge gained thus far in this novel and flourishing field of research, elucidating the key biological and molecular mechanisms whose modulation may represent a viable approach for regenerating the human damaged myocardium.